Accounting Sciences theses: an analysis of their dissemination - Jacqueline Veneroso Alves da Cunha (FUCAPE Business School, 2010)
When a thesis is defended it moves to the condition of scientific literature, serving as a source of knowledge to other authors, thus, playing their role in the construction process and scientific development. The purpose of this study was to find evidences to allow assessing the degree of dissemination of doctoral theses in Accounting (defended in Brazil up to 12/31/2006), in the production of new knowledge. An empirical-analytical approach was used by employing bibliographic and documental research, as well as bibliometric analysis. References to doctoral theses of all articles in proceedings of USP Controllership and Accounting Conferences from 2001 to 2007 were analyzed and catalogued. Most referenced theses belong to the 90s, suggesting that a study cannot be automatically considered old or old-fashioned. Findings show a low number of quotes of theses in general (on average, 2.62% of total citations of all research materials).